Indication and Symbolic Language in Araesol-Bayan of Rouzbehan Baqli: Interpretation or Paraphrase? - محمدبیگی شاهرخ; کمالی ثمین (LANGUAGE ART, 2017)
Since the beginning of Islam, Muslims have tried to achieve a deeper and more accurate understanding of God’s Word by the interpretation of Quran. During this period, various types of interpretations have been formed that one of them is mystical interpretation. Among those who have shown interest in this kind of interpretation, name of Rouzbehan Baqli, who has created significant works, is familiar and controversial. In this article, the main significant interpretation of him, Araesol-Bayan fi Haghayeghel-Quran, has been discussed in two parts; in the first part, independent articles which have been written about the interpretation of Rouzbehan have been presented and assessed. In the second part, by comparing interpretations of two verses of the Holy Quran from Araes and Kashfol-Asrar Meybodi, the performance of both authors, based on standards of writing mystical interpretation are measured. The results show that Araesol-Bayan is not a "mystical interpretation", and its writing quality is close to a special kind of "mystical paraphrase"; Rouzbehan, in this work, almost did not follow any regulations of writing a mystical interpretation; so the most successful researches in analyzing the effect of Rouzbehan are those whose analyses were based on the nature of the "mystical paraphrase" and "thought school of Rouzbehan". Thus in this paper, Araes has been studied from a scientific point of view.